Building Consumer Trust Through A Story-Selling Approach To Tiktok Affiliate Content: A Descriptive Qualitative Research - Salma Elya Rahmi; Rinaldi Rinaldi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The transformation of the contemporary digital commerce ecosystem has radically shifted promotional paradigms from direct selling (hard selling) toward persuasive communication strategies grounded in narrative. This study examines in depth how the story-selling approach in TikTok affiliate content is operationalized as a strategic instrument for building consumer trust, which constitutes a crucial prerequisite for purchase decision-making in the social commerce environment. Employing a descriptive qualitative approach combined with digital ethnography, this research focuses on deconstructing narrative elements, projecting communicator credibility, and constructing emotional closeness in five top- performing beauty affiliate contents in Indonesia. Qualitative data analysis derived from observations of video structure and audience interactions was triangulated with secondary performance metrics extracted from Kalodata.com to assess the consistency between narrative structure and levels of commercial conversion. The findings indicate that story selling manifests through five specific patterns: narratives of routine and promised benefits, visual simplicity, community responsiveness, price-shock effects, and promotional urgency triggers. Each of these patterns activates distinct psychological dimensions of trust. Routine-based narratives were found to significantly reinforce cognitive trust, leading to high qualitative conversion rates, whereas price-shock narratives stimulated affective trust and generated massive social interaction. This study contributes to the literature on digital consumer behavior by conceptualizing how parasocial closeness and narrative authenticity can reduce consumers’ cognitive resistance, while also providing a tactical foundation for creators and business entities in designing affiliate mark eting campaigns centered on trust-building architecture.